Cosmopolitan Urbanism and Architecture & Paradigm Change in Research and Education in in Asia - Johannes WIDODO Associate Professor, Dr. (Journal of Architecture and Wetland Environment Studies, 2012)
Abstract The genesis of human settlements is a continuous process of production and layering of spaces in different scale levels across historical periods. The architectural production in our Asian context is always cosmopolitan, hybrid and eclectic, due to historical links and inclusive cultural attitude. Our common building typologies – and also our modernization processes - are the product of the cosmopolitan communities, the articulation of the multi-layered tangible and intangible traditions, and the direct response to local micro-climate of this region. Diversity, eclecticism, fusion, acculturation, adaptation, can perhaps best describe the nature of our architecture and urbanism.   Our architectural education now is in dire needs to develop a design-research culture to deal with social and environmental changes. Contemporarily we are in an urgent need to find resolutions to address serious problems posed by the climate change, ideological conflicts, economic greed, depletion of resources, and social justice. Research in architecture should be based on the reality on the ground and not just based on alien theories. Design should be based on the understanding of the real contextual problems, to formulate sensible, sensitive, and holistic solutions.   Learning the lessons and wisdoms from our cosmopolitan architecture and urbanism is an important and necessary step towards the improvements and paradigm change in architectural education, research, and practice in Asian context.